Buying styles [electronic resource] : simple lessons in selling the way your customer buys - Wilkinson, Michael , 1957- (American Management Association, 2009)
Presents a fictional situation in which a salesperson has just lost a major sale... and decides to find out why. This book contains tips, checklists, and on-the-go references, that unveils insights for successfully selling to anyone.